Electronic Transmission of Fatty Acids Investigation Data - Adomkus, T.; Adomkienė, R.; Stankevičius, H.; Stankevičienė, M. (Elektronika ir Elektrotechnika, 2009)
Biochemical research, like investigations of many other sciences, uses various analyses methods and multiplex modern equipment. Effective exchange of information among scientists of different biochemistry areas, research groups and laboratories all over the world is essential. Fast and effective transfer of scientific data and information with contemporary services of telecommunications is very important that empower scientists to make decisions immediately. The Internet with multifunctional and variety of structures and dynamics of development is used to provide complex multiple telecommunication services. The biggest shortage of the traditional “best effort” model is that it does not guarantee the quality of services demands, especially for the interactive real time services. In order to ensure the necessary quality of the service (QoS) it must be reacted adequately into the dynamic changes of the load in the network, i.e. the appropriate recourses of the network and the quality of the service must be ensured. In this paper we are proposing the new adaptive (AFQ) scheduling for QoS management model, reasoned by the virtual queue and dynamic weighted queues service coefficient , changing according to the evaluation of the packet state in the node, reasoned by delay target time and present network load. Real investigation data of fatty acids of human hepatoma cells and data transfer with telecommunication service possibilities are shown in this research paper. Ill. 8, bibl. 12, tabl. 2 (in English; abstracts in English, Russian and Lithuanian).